Advancing cleaner municipal waste transport through carbon accounting in the cap-and-trade system. (January 2023) - Peng, He; An, Chunjiang; Ng, Kelvin Tsun Wai; Hao, Jianli; Tian, Xuelin
Graphical abstract: Abstract: Promoting cleaner municipal solid waste transportation processes plays a key role in sustainable waste management. In this study, a regional cap-and-trade system as an incentive tool was developed and applied to waste disposal in Montreal, Canada. The full life-cycle carbon emissions of a waste transport fleet, including four alternative energy scenarios, were accounted for using the GHGenius life cycle assessment tool. Different carbon caps were also considered, as evidence to support the industry's ongoing low-carbon efforts under Quebec's 2030 green plan. The results revealed that the electric fleet decreased carbon emissions (CO2 -equivalent) by 94.40% when compared to the diesel fleet and achieved a cost savings of 63.13% percent when carbon trading offsets were utilized. Considering all cap tightening, credit offsets, and possible subsidies, the electric fleet outperforms the other options in both economics and emission reductions. The findings have important implications for sustaining the low-carbon municipal waste management.